2020
DOI: 10.1002/jcla.23346
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA PVT1, a novel biomarker for chronic obstructive pulmonary disease progression surveillance and acute exacerbation prediction potentially through interaction with microRNA‐146a

Abstract: Objective This study aimed to investigate the abilities of long non‐coding RNA PVT1 (lnc‐PVT1) and microRNA‐146a (miR‐146a) in predicting chronic obstructive pulmonary disease (COPD) susceptibility and acute exacerbation risk, moreover, to explore the association of lnc‐PVT1 with disease severity, inflammation, and miR‐146a in patients with COPD. Methods A total of 80 acute exacerbation of COPD (AECOPD) patients, 80 stable COPD patients, and 80 healthy controls (HCs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“… 5 , 6 Accumulating studies revealed that lncRNAs participate in the pathogenesis of diseases. 7 , 8 LncRNA metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) was revealed to regulate acute respiratory distress syndrome by affecting the secretion of an inflammatory factor. 9 LncRNA plasmacytoma variant translocation (PVT1) was employed to predict COPD susceptibility based on its link with tumor necrosis factor and interleukin (IL), IL-6, IL-8, and IL-17, and microRNA-146a (miR-146a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 Accumulating studies revealed that lncRNAs participate in the pathogenesis of diseases. 7 , 8 LncRNA metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) was revealed to regulate acute respiratory distress syndrome by affecting the secretion of an inflammatory factor. 9 LncRNA plasmacytoma variant translocation (PVT1) was employed to predict COPD susceptibility based on its link with tumor necrosis factor and interleukin (IL), IL-6, IL-8, and IL-17, and microRNA-146a (miR-146a).…”
Section: Introductionmentioning
confidence: 99%
“…9 LncRNA plasmacytoma variant translocation (PVT1) was employed to predict COPD susceptibility based on its link with tumor necrosis factor and interleukin (IL), IL-6, IL-8, and IL-17, and microRNA-146a (miR-146a). 7 In addition, lnc-small nucleolar RNA host gene 1 (lnc-SNHG1) and lnc-pro-transition associated RNA (PTAR) were revealed to promote the progression of lung cancer by sponging miR-497 and miR-101, respectively. 10 , 11 In this study, LINC00987 was found to be apparently downregulated in COPD tissues.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-146a overexpression eliminated the effects of PVT1 knockdown on prostate cancer cells (28). It should be noted that miR-146a, as a target of PVT1, has been documented as an anti-in ammatory mediator (29), which not only correlates with increased production of anti-in ammatory cytokines TGF-β1 and IL-10 (30), but also distinguishes CAD patients from NCAD patients, as mentioned above. MiR-27b-3p could be another possible mediator to justify the observed correlation between PVT1 and IL-10.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Fabp4 inhibitors suppress inflammation and oxidative stress in murine and cell models of acute lung injury [ 23 ], and suppression of Fabp4 protects against rhabdomyolysis-induced acute kidney injury [ 24 ]. In chronic obstructive pulmonary disease patients, the PVT1 expression positively correlated with the GOLD stage and levels of TNF- α , IL-6, IL-8, and IL-17 [ 25 ]; PVT1 exacerbates the inflammation and cell-barrier injury during asthma by regulating miR-149 [ 26 ]. These findings suggested that Fabp4 and PVT1 might play the role in the therapeutic potential of MSCs in phosgene-induced ALI, and we will research the potential role of them in the phosgene-induced ALI in the following research.…”
Section: Discussionmentioning
confidence: 99%